2017
DOI: 10.1002/ajmg.c.31554
|View full text |Cite
|
Sign up to set email alerts
|

Pain management in the Ehlers–Danlos syndromes

Abstract: Chronic pain in the Ehlers–Danlos syndromes (EDS) is common and may be severe. According to one study, nearly 90% of patients report some form of chronic pain. Pain, which is often one of the first symptoms to occur, may be widespread or localized to one region such as an arm or a leg. Studies on treatment modalities are few and insufficient to guide management. The following is a discussion of the evidence regarding the underlying mechanisms of pain in EDS. The causes of pain in this condition are multifactor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
172
0
4

Year Published

2018
2018
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 143 publications
(186 citation statements)
references
References 83 publications
3
172
0
4
Order By: Relevance
“…Dyspareunia in the general population has been reported in 7.5% of sexually active women, with some geographic variation (3.6% in Australia, 18.6% in Brazil) and higher rates among women post‐partum (24%). One prior review of pain in EDS also noted the occurrence of vulvodynia and dyspareunia. Previous research has found that less than a third of women with pelvic pain report it to a medical provider, thus the already high rates found in this review may underrepresent this problem.…”
Section: Discussionmentioning
confidence: 99%
“…Dyspareunia in the general population has been reported in 7.5% of sexually active women, with some geographic variation (3.6% in Australia, 18.6% in Brazil) and higher rates among women post‐partum (24%). One prior review of pain in EDS also noted the occurrence of vulvodynia and dyspareunia. Previous research has found that less than a third of women with pelvic pain report it to a medical provider, thus the already high rates found in this review may underrepresent this problem.…”
Section: Discussionmentioning
confidence: 99%
“…There are many proposed theories as to the mechanisms of pain in HSD, many of which have been drawn from other pain conditions. Available data suggest increased pain may correlate with repeat subluxations and dislocations, soft‐tissue injury, and/or low nocturnal sleep quality . Some studies suggest that patients with HSD experience hyperalgesia and central sensitization, similar to that experienced with fibromyalgia .…”
Section: Introductionmentioning
confidence: 99%
“…Nonopioid oral analgesics such as acetaminophen, nonsteroidal anti‐inflammatory (NSAID) or cyclooxygenase‐2 (COX2) inhibitor should be maximized first. Topical agents and muscle relaxants can also be helpful . Benzodiazepines should be used only cautiously for short‐term and are poor choices for long‐term use, particularly risky when coprescribed with opioids .…”
Section: Discussionmentioning
confidence: 99%
“…For patients with neuropathic pain, regiment can include a tricyclic antidepressant, serotonin‐norepinephrine reuptake inhibitor, and/or an anti‐epileptic agent. Opioids are rarely needed for the treatment of chronic musculoskeletal pain and are not recommended for neuropathic pain . Narcotics (Opioids and tramadol) should be reserved for acute pain episodes or for those who are inadequately managed after trial of all of the above approaches and should be added on to the above regimen in the lowest effective doses rather than replacing nonopioids.…”
Section: Discussionmentioning
confidence: 99%